Syngas Generation from Methane Using a Chemical-Looping Concept: A Review of Oxygen Carriers - Kongzhai Li; Hua Wang; Yonggang Wei (Journal of Chemistry)
Conversion of methane to syngas using a chemical-looping concept is a novel method for syngas generation. This process is based on the transfer of gaseous oxygen source to fuel (e.g., methane) by means of a cycling process using solid oxides as oxygen carriers to avoid direct contact between fuel and gaseous oxygen. Syngas is produced through the gas-solid reaction between methane and solid oxides (oxygen carriers), and then the reduced oxygen carriers can be regenerated by a gaseous oxidant, such as air or water. The oxygen carrier is recycled between the two steps, and the syngas with a ratio of H2/CO = 2.0 can be obtained successively. Air is used instead of pure oxygen allowing considerable cost savings, and the separation of fuel from the gaseous oxidant avoids the risk of explosion and the dilution of product gas with nitrogen. The design and elaboration of suitable oxygen carriers is a key issue to optimize this method. As one of the most interesting oxygen storage materials, ceria-based and perovskite oxides were paid much attention for this process. This paper briefly introduced the recent research progresses on the oxygen carriers used in the chemical-looping selective oxidation of methane (CLSOM) to syngas.